Coherent light-matter interaction in dense atomic clouds - Fernández, Marcia Frómeta (2023)
The main objective of this research is to study a particular case of light-matter interaction: the scattering of light in dense atomic samples. The regime of high atomic densities is represented by samples where the distance between neighboring atoms is on the order of the wavelength associated with the atomic transition. In this regime, short-range atomic interactions cannot be neglected, and in these systems, we expect to observe significant modifications in collective effects such as subradiance or superradiance. Overall, the propagation of light through this type of system is not well-known to the scientific community, and the existing models work to describe very specific situations. To pave the way for achieving our overall goal, this work proposes an experimental setup to obtain a dense cloud of 88Sr, which is the chemical species we work with in our laboratory. For this purpose, atoms previously trapped using a Magneto-Optical Trap are transferred to a Crossed Optical Dipole Trap. During the optimization and characterization of the optical trap, problems were encountered in producing an image with quantitative information of the atomic ensemble and in transferring a large number of atoms in a very small trapping volume. These problems were resolved with the implementation of a Phase Contrast Imaging system and the implementation of an Optical Molasses as an additional cooling step. Under these conditions, we obtained a cloud that can be suitable for conducting studies on collective effects, transitioning from the dilute to the dense regime. The initial experiments, once our atomic ensemble was prepared, involve measuring the coherent transmission of a low-intensity beam through the cloud. For this purpose, incident light near the resonance of a dipolar transition of the type J = 0 ↔ J = 1 of 88Sr is used, interacting with a homogeneous region of the sample. Simulations of this type of process can be performed using the Coupled Dipole Model, which describes the overall response of light scattering by the sample considering dipole-dipole interactions mediated by light. With this work, we aim to advance the understanding of density effects by comparing the coherent optical response of the dense cloud with the theory based on the Coupled Dipole Model.